Beauty of the beast : breathing new life into organizations - Bellman, Geoffrey M. (Berret-Koehler Pub. San FranciscoUS, 2000)
Presents the organization as simultaneously beauty and beast - blessed and cursed by stakeholders. Acknowledges the ugliness of organizations, but advocates that they be faced and even embraced. Argues that organizations can be changed, transformed and revewed by our choices. Advises that beauty and life in organizations be sought, and presents 12 vital signs including: boundaries; leading by doing; spirit of inquiry; direction; and connection. Presents 20 assertions of better ways to renew organizations, using the 4 captions: the reach for...; roots of...; response to...; and realities of renewal.